Isothermal Transformations in High-Strength Cast Iron - Hasanlı, Ramız; Alıyev, Ilham; Poladov, Nızamı; Azimova, Lala; Tagıyev Taleh (Scientific Journals Publishing House, 2022)
The technological process of manufacturing parts from high-strength cast irons is simpler and more economical than the process of manufacturing parts from steel. Cast irons are less sensitive to stress concentrators and strike loads. Spheroidal graphite cast irons can achieve DI 70 grades even in the cast state. Through hardening heat treatment or additional alloying, it is possible to produce cast irons of higher strength (grades DI 80 and above). As the strength properties of cast irons increase, disadvantages in the form of low ductility and plasticity become increasingly apparent. These problems can be compensated by providing an ausferritic, bainite or bainite-austenitic structure of the metal matrix of cast irons. A good solution is to obtain cast irons with a complex structure of the bainite-ausferrite type. In this regard, the relevance of this work is due to the fact that, in the practice of modern mechanical engineering, high-strength cast irons are increasingly used.
Keywords: ausferritic cast iron; isothermal hardening; spheroidal graphite cast iron